Activation of multiple stress responses in Staphylococcus aureus substantially lowers the minimal inhibitory concentration when combining two novel antibiotic drug candidates - Singleton, Amanda Holstad; Bergum, Olaug Elisabeth Torheim; Søgaard, Caroline Krogh; Røst, Lisa Marie; Olsen, Cecilie Elisabeth; Blindheim, Fredrik Heen; Ræder, Synnøve Brandt; Bjørnstad, Frithjof A.; Sundby, Eirik; Hoff, Bård Helge; Bruheim, Per; Otterlei, Marit (Frontiers in Microbiology, 2023)
The past few decades have been plagued by an increasing number of infections caused by antibiotic resistant bacteria. To mitigate the rise in untreatable infections, we need new antibiotics with novel targets and drug combinations that reduce resistance development. The novel β-clamp targeting antimicrobial peptide BTP-001 was recently shown to have a strong additive effect in combination with the halogenated pyrrolopyrimidine JK-274. In this study, the molecular basis for this effect was examined by a comprehensive proteomic and metabolomic study of the individual and combined effects on Staphylococcus aureus. We found that JK-274 reduced activation of several TCA cycle enzymes, likely via increasing the cellular nitric oxide stress, and BTP-001 induced oxidative stress in addition to inhibiting replication, translation, and DNA repair processes. Analysis indicated that several proteins linked to stress were only activated in the combination and not in the single treatments. These results suggest that the strong additive effect is due to the activation of multiple stress responses that can only be trigged by the combined effect of the individual mechanisms. Importantly, the combination dose required to eradicate S. aureus was well tolerated and did not affect cell viability of immortalized human keratinocyte cells. Our findings demonstrate the potential of JK-274 and BTP-001 as antibiotic drug candidates and warrant further studies.